Effect of human error on the reliability of roof panel under uplift wind pressure. (January 2015) - Hong, H.P.; He, W.X.
Highlights: Human error is a contributing factor for wind damage to houses. A survey of roof panel fasteners is carried out for a specimen house. Missing nail could be modeled using binomial process with a rate of 1.5%. Effect of missing nail on the statistics of the panel uplift capacity is assessed. Influence of the missing nail on the reliability under wind load is investigated. Abstract: Post disaster investigations indicate that the roof damage often occur during strong wind events. Human or construction error could be one of the contributing factors for the observed damage. In this study, a survey was carried out at the IRLBH (The Insurance Research Lab for Better Homes) facility (at the University of Western Ontario) to inspect the quality of construction, especially the fasteners used to fasten the plywood roof panels to the roof trusses. Statistics of missing nails which are required for the fastening are obtained. It was suggested that the occurrence of the missing nail could be modeled using binomial process with the occurrence rate of 1.5%. The effect of the missing nail on the statistics of the panel uplift capacity to wind pressure, which are evaluated using the nonlinear finite element techniques by considering the uncertainty in nail withdrawal behavior, is assessed and compared to those without missing nails. Also, the influence of the missing nail on the reliability of roof panel under wind load is investigated. The implication of the results on the codified design is discussed.